Audit Firm Industry Specialization, Discretionary Accruals and Stock Price Synchronicity - Kommunuri, John (Auckland University of Technology, 2013)
The study investigates the association between earnings quality and stock price synchronicity. Stock price synchronicity is a measure of the relative amount of firm specific information impounded into stock price. Prior literature attests that better information environments have lower synchronicity. Accounting earnings are the major source of information for investors’ decision making and influence stock returns. Investors demand audited financial statements for their informed decision making . It is proposed in this study that accounting earnings of firms audited by industry specialist auditors confirm low synchronicity as they impound better quality information into stock price. Agency theory elucidates the significance of information in a decision-making setting. According to the theory, principals appoint agents (Management) and delegate decision-making tasks to them as they trust that the agents would act in the principals’ best interests. The management of a firm plays a significant role in conveying credible signal to the shareholders and other stakeholders, in the form of disclosures, about the quality of information that is to be disclosed and incorporated into stock prices. The market model suggests that the amount of information that impounds into stock price should be mirrored in stock price synchronicity (R2). My study also provides reliable empirical evidence on the effectiveness of auditing which varies with the industry expertise of auditors. It provides a clear understanding of how audit quality is associated with a firm’s information asymmetry and its stock returns. The monitoring role of auditor helps the principal and other decision makers in obtaining reliable information about the firm. Since auditing is regarded as one of the mechanisms both principals and agents place, if an auditor fails to provide sufficient level of audit quality to their client firms, i.e. fails to reduce information asymmetry between the parties, then obviously there will be less or no demand for audit services. The empirical results of this study show that in New Zealand, industry specialization of audit firms is regarded as a significant element of investor decision making. The results of industry specialization quality explicate that the market regards specialists as credible information providers and the clients of industry specialist auditors exhibit low synchronicity. Prior research shows that discretionary accruals are priced by the market (Subramanyam, 1996). When managers employ specialists, the level of discretionary accruals signals the market about the quality of their earnings. Specialists are expected to differentiate between the opportunistic and informative nature of discretionary accruals and are able to minimize (allow) opportunistic (informative) accruals thereby improve accrual quality. If the market perceives this quality and if that quality synchronizes into stock prices, then the clients of specialists attest low synchronicity compared to the clients of non-specialists. The results show that the discretionary accruals of a firm audited by specialists are comparatively low and have a positive effect on the level of the firm’s synchronicity.
Keywords: Stock Price Synchronicity; Audit quality; Industry specialization; Discretionary accruals; Earnings management